Tale of two species of Stylissa (Porifera: Demospongiae: Scopalinida) from the west and east coasts of India - George, Anita M (Zootaxa, 2022)
Recent collections from the western and southern coasts of India recorded two species of Stylissa Hallmann (Scopalinida, Scopalinidae). Stylissa soestii sp. nov. was collected from St. George Island in Goa, Hare Island in the Gulf of Mannar and the Palk Bay. It has six distinct different morphologies and sizes of styles, in addition to the typical gently curved stout and thin styles characteristic of Stylissa, and two different morphologies of strongyloxeas and rare strongyles. Stylissa carteri (Dendy, 1889) was reported previously from India (Gulf of Mannar and Pearl Banks of Tuticorin) and is redescribed here from populations in Palk Bay, east coast of India, in addition to Muttom, Vizhinjam and Lakshadweep islands, which are the first records of S. carteri from the west coast of India.